2018
DOI: 10.1002/jcb.27557
|View full text |Cite
|
Sign up to set email alerts
|

Construction and comprehensive analysis of dysregulated long non‐coding RNA‐associated competing endogenous RNA network in clear cell renal cell carcinoma

Abstract: Objective This study aimed to assess the long noncoding RNA (lncRNA)‐microRNA (miRNA)‐messenger RNA (mRNA) regulatory network in clear cell renal cell carcinoma (ccRCC) by gene expression analyses. Materials and Methods LncRNA, miRNA, and mRNA expression profiles in ccRCC were obtained from The Cancer Genome Atlas. Differentially expressed lncRNAs, mRNAs (cut‐off: |log 2 [fold change, FC])| > 2.0 and adjusted P < 0.01) and miRNAs (|log 2FC| > 1.5 and adjusted P < 0.01) were unveiled using R. Cox regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 65 publications
4
34
1
Order By: Relevance
“…However, a rare study has explored the role of LINC00460 in KIRC, so this was the first study which found that high expression of LINC00460 is linked to poor prognosis in patients with KIRC. In the previous study, LINC00443 was reported as a tumor suppressor, which was associated with a better prognosis of KIRC, while MIAT was associated with worse prognosis [39][40][41]. In our study, expression and survival analysis of LINC00443 and MIAT revealed the high expression of MIAT and the low expression of LINC00443 in KIRC samples, which was related to poor prognosis and better prognosis, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…However, a rare study has explored the role of LINC00460 in KIRC, so this was the first study which found that high expression of LINC00460 is linked to poor prognosis in patients with KIRC. In the previous study, LINC00443 was reported as a tumor suppressor, which was associated with a better prognosis of KIRC, while MIAT was associated with worse prognosis [39][40][41]. In our study, expression and survival analysis of LINC00443 and MIAT revealed the high expression of MIAT and the low expression of LINC00443 in KIRC samples, which was related to poor prognosis and better prognosis, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…They found lower WT1-AS expression in ccRCC than in normal tissue, and WT1-AS expression level was significantly correlated with prognosis (23). Moreover, a subsequent study revealed that WT1-AS expression can be used as an independent predictor of ccRCC prognosis and that patients with high WT1-AS expression had poorer prognosis (24).…”
Section: Expression Level Of Wilms Tumor 1 Antisense Rna In Malignantmentioning
confidence: 98%
“…32 Furthermore, Liao Li et al pointed out MAT restrained BC cells by up-regulating vascular endothelial growth factor (VEGF) and Wang et al pointed out LINC00472 could be a diagnostic marker in renal tumor. 33 So we conjectured LINC0047 might be a potential treatment option in BC.…”
Section: Discussionmentioning
confidence: 94%